Efficacy of CLARA in recurrent/refractory acute myeloid leukaemia patients unresponsive to FLAG chemotherapy. (2nd January 2018) - Kaya, Ali Hakan; Tekgündüz, Emre; Ilkkiliç, Kadir; Dal, Mehmet Sinan; Merdin, Alparslan; Karakus, Abdullah; Hacioglu, Sibel Kabukcu; Bekdemir, Filiz; Çakar, Merih Kızıl; Dogu, Mehmet Hilmi; Ayyildiz, Mehmet Orhan; Korkmaz, Serdal; et al.
Abstract: We hereby report our multicentre, retrospective experience with CLARA in patients with fludarabine/cytarabine/G-CSF (FLAG) refractory AML. The study included all consecutive R/R AML patients, who received CLARA salvage during October 2010–October 2015 period. All patients were unresponsive to FLAG salvage chemotherapy regimen and did not undergo previous allo-HCT. A total of 40 patients were included. Following CLARA 5 (12.5%) patients experienced induction mortality and 10 (25%) patients achieved CR. 25 (62.5%) patients were unresponsive to CLARA. 7 (17.5%) out of 10 patients in CR received allo-HCT. Median overall survival of patients who achieved CR after CLARA was 24.5 months (8.5–54.5) and 3 months (2.5–5), in patients who underwent and didn't allo-HCT, respectively. Our results indicate that CLARA may be good alternative even in FLAG refractory AML patients and can be used as a bridge to allo-HCT, who have a suitable donor and able to tolerate the procedure.